The effect of environmental, social disclosure, and financial performance on firm value - Muslichah Muslichah (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2020)
This research analyzes the effect of environmental and social disclosure (ESD) on firm value (FV) with financial performance (FP) as an intervening variable. Objects of this research are companies involved in Indonesia Sustainability Reporting Award (ISRA). The samples are companies that participated in the ISRA during the period starting from 2013 to 2016. The sample of this research is 15 companies if the period used four years, then the final number of observations used for further analysis is 60. The result of this study shows four essential findings. First, the direct effect of ESD on FV is not significant, the impact of ESD on FP is positive and significant, the effect of FP on FV is positive and significant, FP mediates the impact of social and economic performance on FV. This finding confirms the application of legitimacy and stakeholder theory in developing countries where stakeholders have no power to pressure corporate management into social and environmental activities. The results also benefit managers and standards setters. For managers, this finding emphasizes that ESD is a crucial factor in legitimizing the company's products in the eyes of stakeholders. For standard makers, the results are useful for them to develop social and environmental reporting guidelines.